Calibration of the simulation parameters of jujubes in dwarfing and closer cultivation in Xinjiang during harvest period - Yao, Shiqi; Shi, Gaokun; Wang, Baoshuai; Peng, Huijie; Meng, Hewei; Kan, Za (International Journal of Agricultural and Biological Engineering, 2022)
In order to obtain accurate contact parameters of jujubes in dwarfing and closer cultivation in Xinjiang during the harvest period, based on the Hertz-Mindlin (no-slip) contact model in EDEM, the contact parameters, including the coefficient of restitution, static friction, and rolling friction, between jujube and machine components have been calibrated through physical and simulation test. The coefficient of restitution, static friction, and rolling friction between the jujubes and steel (jujube-steel) were calculated as 0.33, 0.46, and 0.04, respectively. The coefficient of restitution, static friction, and rolling friction between the jujubes and polyvinyl chloride (PVC) (jujube-PVC) were calculated as 0.39, 0.61, and 0.06, respectively. The optimum contact parameters among jujubes (inter-jujubes) were 0.23, 0.33, and 0.04. The accumulation test was applied for comparing the simulation and testing values of jujube’s repose angle. In the results, the relative error was 1.27% which means the discrete element model and the contact parameters of jujube can be used for the discrete element simulation test. In addition, the results can be adequately used to simulate particle scale mechanics (grain commingling, flow/motion, forces, etc.) of jujube in harvest as well as the design and working mechanism study of post-harvest processing machinery and devices. Keywords: jujube, EDEM, contact parameter, experiment, calibration DOI: 10.25165/j.ijabe.20221502.6006 Citation: Yao S Q, Shi G K, Wang B S, Peng H J, Meng H W, Kan Z. Calibration of the simulation parameters of jujubes in dwarfing and closer cultivation in Xinjiang during harvest period. Int J Agric & Biol Eng, 2022; 15(2): 256–264.